2009
DOI: 10.1109/tasl.2008.2012194
|View full text |Cite
|
Sign up to set email alerts
|

Event-Based Instantaneous Fundamental Frequency Estimation From Speech Signals

Abstract: Abstract-Exploiting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(90 citation statements)
references
References 21 publications
0
90
0
Order By: Relevance
“…The second column in the table shows the number of voiced frames (V(n)) detected in the respective utterance. From the third column on, the numbers represent the GEs obtained from BC and AC speech (GE BC (n)/GE AC (n)), respectively, using Praat's AC and CC [14], YIN [3], SWIPE [4], and EBIFF [5] algorithms. As indicated by the GEs, BC speech produces much less errors compared to AC speech for almost all the methods.…”
Section: Pitch Reference Produced From Bone Conducted Speechmentioning
confidence: 99%
See 2 more Smart Citations
“…The second column in the table shows the number of voiced frames (V(n)) detected in the respective utterance. From the third column on, the numbers represent the GEs obtained from BC and AC speech (GE BC (n)/GE AC (n)), respectively, using Praat's AC and CC [14], YIN [3], SWIPE [4], and EBIFF [5] algorithms. As indicated by the GEs, BC speech produces much less errors compared to AC speech for almost all the methods.…”
Section: Pitch Reference Produced From Bone Conducted Speechmentioning
confidence: 99%
“…Again, results obtained using SWIPE algorithm are seemed to be little biased because the reference file is constructed based on the primary estimates obtained using this method. Though the instantaneous frequency based method [5] works by zero-frequency filtering, it is observed that the filtered signals produced by applying the algorithm on BC speech is more suitable for pitch estimation than AC speech. To summarize, when signals from both the AC and BC channels are available, pitch determination from BC speech can yield superior performance.…”
Section: Pitch Reference Produced From Bone Conducted Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithms for speech-based GCI detection have been widely evaluated using EGG-based references [12], [22], [24]. It is known that the synchronization of EGG and speech signals is affected by the propagation time from the talker's lips to the recording microphone that may be estimated and subtracted to synchronize the two signals.…”
Section: Evaluation Referencementioning
confidence: 99%
“…The multiscale product is a key element in the technique proposed in this paper. Detection of periodicity in the speech has also been explored through analysis of the autocovariance matrix of the speech signal [23], zero-frequency resonator [24] and empirical mode decomposition (EMD) [25]. These non model-based approaches are advantageous because they are well-rooted in signal processing and are not constrained by any particular speech model.…”
mentioning
confidence: 99%